Tranexamic acid in non-traumatic intracranial bleeding: a systematic review and meta-analysis - Bouillon-Minois, Jean-Baptiste (Sci Rep, 2021)
Non-traumatic intracranial bleeding (NTIB), comprising subarachnoid hemorrhage (SAH) and intra-cranial bleeding (ICH) is a significant public health concern. Tranexamic acid (TXA) is a promising treatment with benefits yet to be fully demonstrated. We conducted a systematic review and meta-analysis on the impact of TXA on mortality in NTIB. We searched the PubMed, Cochrane Library, Google Scholar and ScienceDirect databases for studies reporting mortality data following the use of TXA in NTIB for comparisons with a control group. We computed random-effect meta-analysis on estimates of risk and sensitivity analyses. We computed meta-regression to examine the putative effects of the severity of NTIB, sociodemographic data (age, sex), and publication date. Among potentially 10,008 articles, we included 15 studies representing a total of 4883 patients: 2455 receiving TXA and 2428 controls; 1110 died (23%) during the follow-up. The meta-analysis demonstrated a potential of 22% decrease in mortality for patients treated by TXA (RR = 0.78, 95%CI 0.58–0.98, p = 0.002). Meta-regression did not demonstrate any influence of the severity of NTIB, age, sex, length of treatment or date of publication. Sensitivity analyses confirmed benefits of TXA on mortality. TXA appears to be a therapeutic option to reduce non-traumatic intracranial bleeding mortality, particularly in patients with SAH.